Purification and characterization of bacterial aryl alcohol oxidase from sphingobacterium sp ATM and Its uses in textile dye decolorization - Tamboli, Dhawal P.; Telke, Amar A.; Dawkar, Vishal V.; Jadhav, Shekhar B.; Govindwar, Sanjay P. (Biotechnology and Bioprocess Engineering, 2011)
Aryl alcohol oxidase (AAO) produced by dye decolorizing bacteria Sphingobacterium sp. ATM, was purified 22.63 fold to a specific activity of 21.75 mu mol/min/mg protein using anion exchange and size exclusion chromatography. The molecular weight of the purified AAO was found to be 71 kDa using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and confirmed by zymography of AAO using L-dopa. The enzyme showed substrate specificity towards veratryl alcohol, followed by n-propanol. The optimum pH and temperature of purified AAO were found to be 3.0 and 40 degrees C, respectively. The K(m) and V(max) of AAO was 1.1615 mM and 3.13 mM/min when veratryl alcohol was used as substrate. Sodium azide showed maximum inhibition while ethylenediamine tetra acetic acid (EDTA), L-cysteine and dithiothreitol showed slight inhibition. Metal ions also showed slight inhibition. HPLC analysis confirmed the degradation of Direct Red 5B. The metabolite obtained after decolorization of Direct Red 5B was characterized as 3 diazenyl 7 [-(phenyl carbonyl) amino] naphthalene-2-sulfonic acid using GC-MS analysis.
Keywords: aryl alcohol oxidase; Direct Red 5B; dye decolorization; ion exchange chromatography; Sphingobacterium sp ATM

Parasitism by Chelonus blackburni (Hymenoptera) affects food consumption and development of Helicoverpa armigera (Lepidoptera) and cellular architecture of the midgut - Sanap, Yogita; Dawkar, Vishal V.; Giri, Ashok P.; Sen, Avalokiteswar; Pandit, Radhakrishna S. (Journal of Asia-Pacific Entomology, 2016)
Biological control agents are vital components of an integrated pest management strategy, and this is frequently referred to as natural control. Natural enemies of insect pests include predators, parasitoids, and pathogens. Among them, a parasitoid, Chelonus blackburni (Cameron), was found to be the best biological control agent for the polyphagous pest, Helicoverpa armigera (Hubner). C. blackburni alters the feeding performance of H. annigera larvae upon parasitism and as a result severely affects growth and development. Moreover, it shortens the feeding period of H. armigera and increases mortality. Furthermore, total hemocyte count (THC) was significantly decreased in parasitized larvae than control. Parasitized H. armigera had 26% less number of blood cells compared to healthy larvae. Histological studies showed that the structure of midgut of H. annigera is drastically affected by C. blackburni leading to reduced food consumption, which ultimately led to larval death. The present study provides an insight to changes involved in H. annigera due to parasitism by C blackburni, a parasite that could be used as an effective biocontrol agent to manage H. armigera. (C) 2015 Korean Society of Applied Entomology, Taiwan Entomological Society and Malaysian Plant Protection Society. Published by Elsevier B.V. All rights reserved.